2022
DOI: 10.1097/md.0000000000030108
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent respiratory infections and vitamin A levels: a link? It is cross-sectional

Abstract: Respiratory tract infections are common illnesses in children, causing significant morbidity and negatively affecting their health. Vitamin A protects against infections and maintains epithelial integrity. The goal of this study was to determine the correlation between vitamin A deficiency and recurrent respiratory tract infections (RRTIs). Participants in this cross-sectional study were divided into 3 groups: RRTIs (including patients with history of RRTIs presenting with respiratory tract infection symptoms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Previous studies have shown that the disruption of the barrier function of the respiratory tract and impaired immune function may be closely linked with RRTIs. The association between VAD and development of RRTI in children has been found recently (21). VA is a very important fat-soluble vitamin to human and plays an immunomodulatory role in the human body, especially in the maintenance of airway epithelial cell integrity and immune function (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the disruption of the barrier function of the respiratory tract and impaired immune function may be closely linked with RRTIs. The association between VAD and development of RRTI in children has been found recently (21). VA is a very important fat-soluble vitamin to human and plays an immunomodulatory role in the human body, especially in the maintenance of airway epithelial cell integrity and immune function (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have focused on determining the relation between VA concentrations and RTIs (18, 19), whereas only a few studies on the relation between serum VA levels and RRTIs (20)(21)(22). In addition, the association between threshold dietary intake of vitamin A and respiratory outcomes is unclear.…”
mentioning
confidence: 99%
“…In addition to contributing to visual health, vitamin A has fundamental functions in the immune system response [ 11 , 14 ]. Studies have reported that low intake and low serum concentration of vitamin A have been associated with respiratory tract infections [ 42 , 43 ]. Furthermore, according to Sirisinha et al [ 15 ], Wistar rats assigned to a vitamin A-deficient diet exhibited lower concentrations of SIgA in intestinal samples compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A (FDA daily allowance (DA): 900 mcg) has antioxidant properties and its supplementation is used to boost immune function and prevent respiratory infections [ 21 , 22 ]. Despite in vitro evidence of the protective role of vitamin A against cancer in many instances [ 23 ], population-based studies have found an increased risk of certain cancers associated with vitamin A supplementation.…”
Section: Vitaminsmentioning
confidence: 99%